Churg-Strauss syndrome associated with montelukast therapy. Issue 9 (1st September 2000) - Tuggey, J M; Hosker, H S R
Abstract : Churg-Strauss syndrome is a rare form of eosinophilic vasculitis associated with asthma. There have been several recent case reports of the condition in association with leukotriene antagonists and it has been speculated that the Churg-Strauss syndrome was unmasked when oral corticosteroids were withdrawn. We report a case of Churg-Strauss syndrome associated with montelukast therapy in an asthmatic patient in whom there had been no recent oral corticosteroid use. We believe that this is the first such reported case and would suggest that clinicians need to be vigilant in all patients who develop systemic symptoms when starting treatment with leukotriene antagonists.